The effective role of akermanite on the apatite-forming ability of gelatin scaffold as a bone graft substitute - Zare-Harofteh, Azam; Saber-Samandari, Samaneh; Saber-Samandari, Saeed (Elsevier Sci Ltd, 2016)
When implanted in living body, a scaffold plays an important role in guiding new bone formation into desired shapes via the development of a biologically active, bone-like apatite layer on its surface. In this study, akermanite (Akr) nanoparticles were synthesized, and, using freeze-casting method, their different contents were applied in the preparation of porous gelatin (Gel) scaffolds. After, the nanocomposite scaffolds were immersed in a simulated body fluid (SBF) solution for 14 days, the bioactivity and apatite formation on their surfaces were examined. The prepared nanocomposite scaffolds before and after immersion in the SBF solution were characterized via the use of Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD) analysis. In addition, the elastic modulus and compressive strength of the scaffolds, as the candidate's mechanical properties, were investigated. According to the results, the prepared nanocomposite scaffolds with cellular and lamellar morphology exhibited preferentially and regularly oriented pores in the range of 94-125 mu m. Under optimum conditions, the Gel/Akr nanocomposite scaffolds with 93.5% swelling had a compressive strength of 1.1 MPa, an elastic modulus of 102 MPa. In addition, the in vitro bio-mineralization test confirmed that all samples were bioactive, and deposited apatite particles were detected with FTIR, XRD, SEM, and EDS after incubation in the SBF. The swelling ability of the scaffolds when immersed in water and phosphate buffer saline (PBS) was also investigated. The results of this study suggest that the prepared Gel/Akr nanocomposite scaffold that closely mimics the properties of bone tissue could be a promising biomedical material for clinical use in bone tissue engineering. (C) 2016 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Bone tissue engineering; Scaffold; Bioactivity; Akermanite; Gelatin; Freeze-casting